PENGARUH INFLASI, SUKU BUNGA, ROA DAN EPS TERHADAP RETURN SAHAM PERUSAHAAN SUB SEKTOR BATU BARA - Sukmadewi, Made Dian; Badjra, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023DO - 10.24843/EEB.2023.v12.i12.p05, 2023)
Investment is an activity to invest directly or indirectly with the aim of obtaining a return. One form of indirect investment that is popular and in great demand by investors today is stocks. The level of return obtained by investors is not fixed and can change at any time. The purpose of this study was to determine the effect of inflation, interest rates, ROA and EPS on stock returns. This research was conducted using the object of research, namely the coal sub-sector mining sector companies listed on the Indonesia Stock Exchange in the 2016-2020 period. This study uses secondary data from the company's financial statements as well as the official website of Bank Indonesia and the Central Statistics Agency (BPS). The analysis technique used is multiple linear regression. The results show that (1) inflation has no effect on stock returns, (2) interest rates have a negative effect on stock returns, (3) ROA has a positive effect on stock returns, and (4) EPS has a positive effect on stock returns.